Fast emerging insecticide resistance in Aedes albopictus in Guangzhou, China: Alarm to the dengue epidemic. - Xinghua Su; Yijia Guo; Jielin Deng; Jiabao Xu; Guofa Zhou; Tengfei Zhou; Yiji Li; Daibin Zhong; Ling Kong; Xiaoming Wang; Min Liu; Kun Wu; et al. (Public Library of Science (PLoS), 2019)
Dengue is one of the most serious mosquito-borne infectious diseases in the world. Aedes albopictus is the most invasive mosquito and one of the primary vectors of dengue. Vector control using insecticides is the only viable strategy to prevent dengue virus transmission. In Guangzhou, after the 2014 pandemic, massive insecticides have been implemented. Massive insecticide use may lead to the development of resistance, but few reports are available on the status of insecticide resistance in Guangzhou after 2014. In this study, Ae. albopictus were collected from four districts with varied dengue virus transmission intensity in Guangzhou from 2015 to 2017. Adult Ae. albopictus insecticide susceptibility to deltamethrin (0.03%), permethrin(0.25%), DDT(4%), malathion (0.8%) and bendiocarb (0.1%) was determined by the standard WHO tube test, and larval resistance bioassays were conducted using temephos, Bacillus thuringiensis israelensis (Bti), pyriproxyfen (PPF) and hexaflumuron. Mutations at the voltage-gated sodium channel (VGSC) gene and acetylcholinesterase (AChE) gene were analyzed. The effect of cytochrome P450s on the resistance of Ae. albopictus to deltamethrin was tested using the synergistic agent piperonyl butoxide (PBO). The results showed that Ae. albopictus populations have rapidly developed very high resistances to multiple commonly used insecticides at all study areas except malathion, Bti and hexaflumuron. We found 1534 codon mutations in the VGSC gene that were significantly correlated with the resistance to pyrethroids and DDT, and 11 synonymous mutations were also found in the gene. The resistance to deltamethrin can be significantly reduced by PBO but may generated cross-resistance to PPF. Fast emerging resistance in Ae. albopictus may affect mosquito management and threaten the prevention and control of dengue, similar to the resistance in Anopheles mosquitoes has prevented the elimination of malaria and call for timely and guided insecticide management.